Village (Gampong) Owned Enterprises with Local Wisdom Between Opportunities and Threats in The Area Of COVID-19 Pandemic (Research at The Government Environment of Lhokseumawe City) - Muhammad Muhammad; Hadi Iskandar; Rasyidin Rasyidin; Juni Ahyar; Rudi Kurniawan (Jurnal Manajemen Pelayanan Publik, 2021)
Before the emergence of Covid-19 which developed throughout the world, the Indonesian Central Government had issued Law Number 6 of 2014 concerning Villages, which is a policy that regulates the level of Village administration. However, in this law there is no allocation of development funds and village empowerment which is the basis of the community at the level of village government administration (Gampong). Funds sourced from APBN, APBD Province or Regency, hope to support the progress of the village to become an independent village capable of organizing and managing. The allocation of village funds in the form of a Village Revenue and Expenditure Budget (APBG) is directed to finance government activities, development and community empowerment. For this reason, the Government has issued a special policy to handle Covid-19 by allocating Village Funds to address problems arising from the Covid-19 pandemic. Especially for the economic sector through the formation of Village-Owned Enterprises (BUMG) which is a business driver to improve the quality of life and realize the welfare of rural communities. With a descriptive qualitative approach using three methods, namely observation, interviews and documentation analysis. This study aims to determine business potential with local wisdom through a SWOT analysis with a focus on Village-Owned Enterprises. Based on the SWOT analysis, in the end, Village-Owned Enterprises will facilitate activities in realizing plans in accordance with local wisdom for the welfare of the community, especially in the era of the Covid-19 pandemic.